O uso da música como ferramenta motivacional no processo de aprendizagem da língua inglesa na escola Irmã Santina Rioli em Macapá/AP - SIMIÃO, Clara Caroline Maia (UNIFAP – Universidade Federal do Amapá, 2022)
This work comes to perform a case study in which to be referring to the use of music as a learning strategy’s English language (EL), for theoretical construction were used the concepts of micro-ability of oral comprehension for which a related music was selected with the contents of the lesson with the cloze tool such as erasing and replacing a word with a gap. The music is featured as a great ally and is very useful as a motivating factor for EL lessons. In this sense, the teaching of English language, like the other subjects, needs to have a constant search in providing the intrinsic motivation in the student from a motivation. As noted in the study site the advantages of using music in language teaching, is the accessibility of oral English and pronunciation. With the activities it can be seen that the rhymes allow the students exercises of identification of similar sounds a better understanding and understanding of the EL making it more significant.